Advances in therapeutic vaccines for treating human papillomavirus‐related cervical intraepithelial neoplasia. Issue 7 (10th May 2020) - Barra, Fabio; Della Corte, Luigi; Noberasco, Giovanni; Foreste, Virginia; Riemma, Gaetano; Di Filippo, Claudia; Bifulco, Giuseppe; Orsi, Andrea; Icardi, Giancarlo; Ferrero, Simone
Abstract: Aim: Human papillomavirus (HPV) is the etiologic agent of the majority of cervical intraepithelial lesions (CIN) and cervical cancers. While prophylactic HPV vaccines prevent infections from the main high‐risk HPV types associated with cervical cancer, alternative nonsurgical and nonablative therapeutics to treat HPV infection and preinvasive HPV diseases have been experimentally investigated. Therapeutic vaccines are an emerging investigational strategy. This review aims to introduce the results of the main clinical trials on the use of therapeutic vaccines for treating HPV infection and ‐related CIN, reporting the ongoing studies on this field. Methods: Data research was conducted using MEDLINE, EMBASE, Web of Sciences, Scopus, ClinicalTrial.gov, OVID and Cochrane Library querying for all articles related to therapeutic vaccines for the treatment of HPV‐related CIN. Selection criteria included randomized clinical trials, nonrandomized controlled studies and review articles. Results: Preliminary data are available on the evaluation of therapeutic vaccines for treating cervical HPV infections and CIN. Despite having in vitro demonstrated to obtain humoral and cytotoxic responses, therapeutic vaccines have not yet clinically demonstrated consistent success; moreover, each class of therapeutic vaccines has advantages and limitations. Early clinical data are available in the literature for these compounds, except for MVA E2, which reached the phase III clinical trial status, obtaining positive clinical outcomes. Conclusion: Despite promising results, to date many obstacles are still present before hypothesize an introduction in the clinical practice within the next years. Further studies will draw a definitive conclusion on the role of therapeutic vaccines in this setting.